The Role of Narrative Format in Improving Narrative Transport and Empathy among Fiction and Non Fiction Readers - Setiawati Intan Savitri; Farhah Kamilatun Nuha (Jurnal Psikologi, 2021)
The purpose of this study was to determine whether non-fiction (news) and fiction (short story) narrative formatscould have different effects in increasing narrative transport and readers’ empathy. The study was conductedusing an experimental pre-posttest method and two groups designed. Participants of 62 students (male = 19,female = 43, Mage= 21.6) were randomly assigned to two groups of reading conditions (non-fiction vs. fiction),then their level of empathy and narrative transport were measured after manipulation/treatment. The measuresused were the Narrative Transport Questionnaire and the Interpersonal Reactivity Index. The statistical analysismethod used was the MANCOVA test. Differences in conditions (non-fiction vs. fiction) as independentvariables, baseline narrative transport score and empathy as covariates to be controlled. The test results betweenthe group multivariate test showed that there was a significant difference between the reading groups of non-fiction and fiction on narrative transport and readers’ empathy simultaneously after controlling for the pre-testnarrative transport and pre-test empathy variables, F(2, 57) = 3.291, p < .05, Wilks’ Λ = .896, with power ηp2 =.104 (10.4%). The univariate test on each dependent variable (empathy, narrative transport) in terms of textreading (non-fiction vs. fiction), after controlling for covariates (pre-test empathy, pre-test narrative transport),only differed significantly in the dependent variable narrative transport, F(5, 55) , p < 0.05, with ηp2 = .087 (8.7%),but not significant on the dependent variable empathy. The discussion is related to the familiarity of the readertowards the main character in non-fiction and fiction texts